Students’ self-regulation and motivation in learning science - Tanti Tanti; Maison Maison; Boby Syefrinando; Mahbub Daryanto; Hayyu Salma (Institute of Advanced Engineering and Science, 2020)
The student's self-regulation and motivation are essential for students to study. Especially with 21st-century learning students are required to be more active in learning than teachers. This Mixed Methods research aimed to determine the influence between the students' self-regulation with the motivation of students learning. The sample size was 534 students from Madrasah Tsanawiyah in Jambi city, Indonesia determined by total sampling technique. Data were then analyzed with the SPSS 21 application to find descriptive statistics as well as inferential statistics using simple regression and for comparison using the independent sample T-Test. The results of this research are dominant in both self-regulation and student motivation in learning, which is strengthened by the relationship and influence between self-regulation and the motivation of students in learning. It is seen from the value of sig = 0.019 and has a contribution of 70.3%. According to the results, it is recommended that students need to be given the opportunity to conduct learning directly and teachers must perform innovative learning.